Robots integrated with virtual reality simulations for customized motor training in a person with upper extremity hemiparesis: a case report - Fluet, Gerard G. (2012)
BACKGROUND AND PURPOSE: A majority of studies examining repetitive task practice facilitated by robots for the treatment of upper extremity paresis utilize standardized protocols applied to large groups. Others utilize interventions tailored to patients but don't describe the clinical decision making process utilized to develop and modify interventions. This case report will describe a robot-based intervention customized to match the goals and clinical presentation of a gentleman with upper extremity hemiparesis secondary to stroke. METHODS: PM is an 85 year-old man with left hemiparesis secondary to an intracerebral hemorrhage five years prior to examination. Outcomes were measured before and after a one month period of home therapy and after a one month robotic intervention. The intervention was designed to address specific impairments identified during his PT examination. When necessary, activities were modified based on the patient's response to his first week of treatment. OUTCOMES: PM trained twelve sessions using six virtually simulated activities. Modifications to original configurations of these activities resulted in performance improvements in five of these activities. PM demonstrated a 35 second improvement in Jebsen Test of Hand Function time and a 44 second improvement in Wolf Motor Function Test time subsequent to the robotic training intervention. Reaching kinematics, 24 hour activity measurement and the Hand and Activities of Daily Living scales of the Stroke Impact Scale all improved as well. DISCUSSION: A customized program of robotically facilitated rehabilitation resulted in large short-term improvements in several measurements of upper extremity function in a patient with chronic hemiparesis.